Correction: The Burden of Leprosy in Cameroon: Fifteen Years into the Post-elimination Era. - Earnest Njih Tabah; Dickson Shey Nsagha; Anne-Cecile; Martin W Bratschi; Theophilus Ngeh Njamnshi; Gerd Pluschke; Alfred Kongnyu Njamnshi (Public Library of Science (PLoS), 2017)
[This corrects the article DOI: 10.1371/journal.pntd.0005012.].